1997
DOI: 10.1002/(sici)1096-9071(199705)52:1<77::aid-jmv12>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Common origin of human T-lymphotropic virus type-I from Iran, Kuwait, Israel, and La Réunion Island

Abstract: We found previously that Kuwaiti HTLV-I isolates had two nucleotide substitutions in the most frequently sequenced regions of HTLV-I genome, namely: T-->C 4783 in the pol and T-->C 6569 the env genes. These substitutions were observed rarely in other HTLV-I isolates and seemed to be good markers of the HTLV-I lineage, the "epicentre" of which was located in Mashhad, Iran. To test this hypothesis we sequenced the fragments of HTLV-I genome including sites 4783 and 6569 from seven isolates obtained from the Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…33 Despite the common origin and similarity of the virus in the region, different prevalences of HTLV-I have been reported in countries near Iran such as Kuwait, Iraq, and Turkmenistan. [34][35][36] Furthermore, the social interaction among countries such as international trade, tourism, and pilgrimage seems to be playing a pivotal role in virus distribution. 37 In fact, the real reason for the extreme variation of the prevalence of HTLV-I in the continents, the countries, or even in different parts of a country is a challenging issue; thus, it is difficult to explain the FIG.…”
Section: Discussionmentioning
confidence: 99%
“…33 Despite the common origin and similarity of the virus in the region, different prevalences of HTLV-I have been reported in countries near Iran such as Kuwait, Iraq, and Turkmenistan. [34][35][36] Furthermore, the social interaction among countries such as international trade, tourism, and pilgrimage seems to be playing a pivotal role in virus distribution. 37 In fact, the real reason for the extreme variation of the prevalence of HTLV-I in the continents, the countries, or even in different parts of a country is a challenging issue; thus, it is difficult to explain the FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The family roots in three described Kuwaiti patients were located to Iraq in Najaf, which population had historically strong ties with the Mashdad region of Iran. Molecular characterization of HTLV-1 found revealed close similarity with HTLV-1 isolates originating from Mashhad in these Kuwaiti patients, suggesting the common origin of Kuwaiti (Najafi) and Mashhadi HTLV-1 infection [26,27]. In addition, a relatively high prevalence of HTLV-1 infection (1:4648) was found among volunteer blood donors in Kuwait [28].…”
Section: Discussionmentioning
confidence: 71%
“…Subsequent studies confirmed, that a relatively high prevalence of HTLV-I infection can be detected in Israel, confined almost exclusively to the immigrants from Mashhad, in so-called Mashhadi Jews. Then it has been shown that the high prevalence of HTLV-I infection is also characteristic for the Muslim population of Mashhad and for additional regions in Iran [25,26]. A low prevalence and sporadic cases of HTLV-I has been described in Iraq and, more recently, in Kuwait [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the HTLV-1 infection in Israel is limited to Jews originating from Iran, mostly from Mashhad. [11] Therefore, controversy of association of MF and HTLV-1 from one side and endemic status of MF in Iran from another side, persuaded us to retrospectively investigate on the rate of HTLV-1 infection in Iranian MF patients and compare it with its normal rate in Iranian population in a case-control study.…”
mentioning
confidence: 99%